Quantitative Expression of TYR, CD34, and CALD1 Discriminates Between Canine Oral Malignant Melanomas and Soft Tissue Sarcomas - Tsoi, Mayra F.; Thaiwong, Tuddow; Smedley, Rebecca C.; Noland, Erica; Kiupel, Matti (Frontiers in Veterinary Science, 2021)
Canine oral malignant melanomas (OMMs) exhibit a variety of morphologic phenotypes including a spindloid variant. The microscopic diagnosis of spindloid OMMs is based on junctional activity and/or the presence of melanin pigment. In the absence of these features, spindloid OMMs are difficult to differentiate from soft tissue sarcomas (STS). An antibody cocktail (MDX) that includes Melan-A, PNL2, tyrosinase-related proteins 1 and 2 (TRP-1 and TRP-2) is the current gold standard for identifying amelanotic OMMs by immunohistochemistry (IHC). However, MDX is less sensitive for diagnosing spindloid amelanotic OMMs. This raises concern for biopsy specimens that lack overlying epithelium, making it potentially difficult to differentiate OMM from STS by IHC. The goal of this study was to identify additional markers to help differentiate between STS and OMMs that lack pigment and junctional activity. SOX-10 has recently been proposed as a sensitive marker for melanocytes in humans but has not been validated in dogs. Similarly, RNA expression for various genes has been analyzed in humans, but not in the context of diagnosing canine melanocytic neoplasms. For this retrospective study, formalin fixed, paraffin embedded tissues from 20 OMMs, 20 STS, and 20 oral spindle cell tumors (OSCTs) that lacked junctional activity and pigmentation were selected. IHC for MDX, SOX-10 and laminin, in parallel with RT-qPCR of TYR, SOX10, CALD1, CD34, DES, and LAMA1, was performed on all cases. TYR, CD34, and CALD1 were the most discriminatory genes in differentiating between OMM and STS, all having 100% specificity and 65%, 95%, and 60% sensitivity, respectively. While all 20 OMMs immunohistochemically labeled for SOX-10, two STS also labeled (100% sensitivity, 90% specificity). MDX IHC labeled all 20 OMMs and no STS. Surprisingly, none of the 20 OSCTs expressed TYR RNA above the cut-off, and 14/20 OSCTs expressed CALD1 or CD34 RNA above the cut-off, thereby confirming them as STS. Four OSCT were suspect STS, and no OSCTs were confirmed as OMMs based on IHC and RNA expression patterns. In conclusion, RNA levels of TYR, CD34 and CALD1 should be evaluated in suspected amelanotic OMMs that are negative for MDX to accurately differentiate between OMM and STS.